Criminalization of Corruption and Maximization of Asset Recovery in a Political and Legal Perspective (PT Asabri Case Study) - Zahra Putri Pertiwi; Indah Sri Utari (Universitas Negeri Semarang, 2026)
This paper explores strategies to enhance the restitution of government financial losses resulting from corrupt practices in the financial administration of the state-owned enterprise PT Asabri (Persero). The results of the research show that PT Asabri's finances are part of the state's finances, so that every corruption crime that occurs in it has consequences in the form of state losses that must be recovered through available legal mechanisms. Criminal law enforcement has been implemented, including the imposition of supplementary sanctions requiring restitution payments to the state as a mechanism for recovering public finances. However, this mechanism has not been able to restore all state losses caused by corruption crimes. The main obstacle in the recovery of state losses stems from the provisions of Article 18 paragraph (1) b of the Law on the Eradication of Corruption Crimes which limits the payment of compensation money to only the value of the assets obtained by the perpetrators of corruption crimes. These restrictions cause the convict's liability only includes the return of economic benefits obtained illegally, while other state losses arising from corruption crimes at PT Asabri cannot be fully held accountable to the convict. In fact, in practice, corruption has the potential to cause wider state losses, not limited to wealth that is directly controlled or enjoyed by the perpetrator.